Alat Ukur Kadar Karbon Monoksida (Co)Dan Hidrokarbon (Hc) Gas Buang Kendaraan BermotorDengan Penampil Smartphone Android - s, Anton; , Dr. Heru Supriyono, M.Sc (2017)
Motor vehicle exhaust emissions containing harmful pollutant gases that can damage the environment and health problems in humans. For controlling the emission levels of vehicles, made gauges the levels of exhaust emissions of motor vehicles. Making this tool aims to facilitate consumer determine levels of motor vehicle exhaust emissions. The hardware used in this tool include Smartphone as a viewer, Arduino modules as the brains of these tools, the Bluetooth module as an intermediary between the device with arduino, and sensors as content measuring gases resulting from combustion engine vehicles, while the software used on the appliance These include Arduino and Android studio. The method used in this study is an experimental method that consists of data collection, data analysis, making tools and testing tools. Carbon monoxide (HC) and hydro carbon (CO) can be measured and monitored by looking at the data displayed android smartphone. Testing is done with two categories, namely: measurement with rpm 0 and measurements with rpm 2000. Based on the results of tests performed, unknown percentage of errors of measurement with rpm 0, ie 1ppm to HC and 0,0075% for CO, whereas the measurement with rpm 2000 ie 2ppm to HC and 0,0075% for CO. The error is likely to occur due to the ability of gas sensor MQ-2 and MQ-7 were less sensitive measure gas levels with a variety of disorders.